Uma revisão sistemática do ensino de matemática para estudantes com Transtorno do Espectro Autista - Abreu, Karina de Kassia (2020)
Educators deal daily with the difficulties in attending the multiple forms of learning of their students, especially those diagnosed with Autistic Spectrum Disorders (ASD). Thus, on of the objectives of this study was organize and analyse teaching materials, teaching practices, digital technologies and their contributions to the teaching and learning process. The main question to be answered was "What are the challenges and the prospects for teaching mathematics to students with ASD?". The applied methodology was a systematic review of 47 studies carried out in Brazil (13 studies) and abroad (34 studies). The studies were researched on the Google Academic and Scopus platforms. The data were organized in 11 distincts categories. The analysis suggested that there is an advance built in this aspect of study, mainly in Brazil, but there are gaps that should be explored as research of didactic sequences focused on thematic axis of Algebra and Geometry, with a focus on developing coherent skills studied in high school. Also, it is important develop research that are applied in a common classroom, developing the mathematical skills of the subject with ASD together with social skills, and research that aims to assist and promote pedagogical tools for individuals with High Functioning Autism / Asperger’s Syndrome. As a final result, the highlights and limitations of the studies found in this bibliographic survey were synthesized, as well as using in the teaching-learning process: modeling and perspective videos, repetition commands, pre-defined instructions sequentially; and yet, it is suggestive to use or produce virtual platforms that have a simple and direct layout, with little information to meet the needs of students with ASD in the teaching of mathematics; among other considerations.